2022
DOI: 10.1111/hae.14492
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported outcomes in autosomal inherited bleeding disorders: A systematic literature review

Abstract: Aim Currently, it is unknown which patient‐reported outcomes are important for patients with autosomal inherited bleeding disorders. Therefore, the purpose of this study is to systematically review the available literature assessing patient‐reported outcomes and their measurement methods in autosomal inherited bleeding disorders. Methods The Embase, Medline ALL, Web of Science Core Collection, Cochrane Central Register of Controlled Trails and Google Scholar databases were searched from inception until 14 Augu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Before the first Delphi round, a long list of health outcomes was developed based on the long-list used by the CoreHEM and Haemovalue initiatives on health outcomes for persons with hemophilia [ 12 , 19 ]. These long-lists were enriched with the findings of a systematic review on patient-reported outcomes in patients with autosomal inherited bleeding disorders [ 14 ]. A plain language definition was provided for each health outcome.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the first Delphi round, a long list of health outcomes was developed based on the long-list used by the CoreHEM and Haemovalue initiatives on health outcomes for persons with hemophilia [ 12 , 19 ]. These long-lists were enriched with the findings of a systematic review on patient-reported outcomes in patients with autosomal inherited bleeding disorders [ 14 ]. A plain language definition was provided for each health outcome.…”
Section: Methodsmentioning
confidence: 99%
“…It is uncertain whether these identified health outcomes that are important for persons with hemophilia are transferable to patients with autosomal inherited bleeding disorders. Whereas the hemophilia population largely consists of men, a large proportion of patients with autosomal inherited bleeding disorders comprises females, who experience sex-specific health outcomes, such as menorrhagia and pregnancy complications [ 14 , 15 ]. Therefore, this study aimed to assess which health outcomes are important specifically for patients with autosomal inherited bleeding disorders, consisting of von Willebrand disease, platelet function disorders, and rare bleeding disorders, from the patients’, caregivers’, and healthcare professionals’ perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…3 Bleeds cause fear and impairment in physical functioning that negatively affects health-related quality of life (HRQoL). 4 Haemophilia B treatment currently involves FIX replacement with either standard or extended half-life products. 1,5 FIX replacement adherence can be difficult, with 25% of people with haemophilia aged 18−30 years being non-adherent, and some choosing to decrease their dosing frequency to mitigate this burden.…”
Section: Introductionmentioning
confidence: 99%
“…Joint bleeds are a major concern, resulting in chronic pain, long‐term joint damage and mobility deficits 3 . Bleeds cause fear and impairment in physical functioning that negatively affects health‐related quality of life (HRQoL) 4 …”
Section: Introductionmentioning
confidence: 99%
“…Social and economic factors are essential for the protection of health. Patients with autosomal inherited bleeding disorders report lower health related quality of life, especially those with joint bleeds [1]. In the case of people with hemophilia or other coagulopathies, apart from providing them with the medical treatment they need it is important to help them acquire the strategies required to deal with the physical, emotional, and social challenges they are likely to encounter at the different stages of their lives [2,3].…”
Section: Introductionmentioning
confidence: 99%